Mobile phone applications in academic library services: a students' feedback survey - Abdul Karim, Nor Shariza; Darus, Siti Hawa; Hussin, Ramlah (Emerald Group Publishing Limited, 2006)
Purpose – This study seeks to explore the utilization of mobile phone services in the educational environment, explore the nature of mobile phone use among university students, and investigate the perception of university students on mobile phone uses in library and information services. Design/methodology/approach – The study used a review of literature to investigate about the nature of wireless phone application in education institution and a survey to collect data from 206 undergraduate students from two academic faculties in a Malaysian public university to explore the respondents’ perception and the nature of wireless phone use. Findings – The respondents’ perceptions on the application of wireless hand services in the context of library and information services were found to be very positive. A high majority of the respondents indicated their willingness to become the users of such services if offered. Research limitations/implications – Limitations in this study are related with the ability of the result to be generalized to other user groups. More research needs to be conducted on the interface design and retrieval to ﬁt information in a much smaller application device that is also limited by a smaller bandwidth. Practical implications – The ﬁndings should assist information providers such as libraries and telecommunication service providers in designing the system that allows for effective access to various information and library services using mobile phones. Originality/value – This study should be an eye opener for both the researcher and the practitioners that the wireless application services are still lacking, despite the increasing needs from the users.